ESG Performance and Its Impact on Mitigating Cost of Capital: Evidence from Southeast Asia - Saputra, Anggi; Rahman, Annisaa (E-Jurnal Akuntansi; Vol 34 No 8 (2024), 2024)
In response to global challenges such as climate change, social injustice, and the growing demand for corporate ethics, Environmental, Social, and Governance (ESG) factors have become central to business, investment, and public policy agendas. This study aims to provide empirical evidence on the impact of ESG performance on the cost of capital. The research sample consists of non-financial companies listed on stock exchanges in developing Southeast Asian countries from 2018 to 2023. Using panel data regression analysis with STATA version 17, the findings reveal a significant positive relationship between overall ESG performance and the environmental pillar's impact on the cost of capital. However, the social and governance pillars do not show a significant effect on the cost of capital. Further analysis reveals that while ESG performance significantly reduces the cost of debt, it has no impact on the cost of equity. These results suggest that ESG-related practices are not yet fully valued by capital markets and stakeholders in developing Southeast Asian countries. Keywords: Environmental score, Social score, Governance score, ESG performance, Cost of Capital